Depot formulations to sustain periocular drug delivery to the posterior eye segment. Issue 8 (August 2019) - Agban, Yosra; Thakur, Sachin S.; Mugisho, Odunayo O.; Rupenthal, Ilva D.
Highlights: Transscleral drug delivery may offer an advantage when treating choroidal diseases. The periocular space can hold larger drug formulation volumes than the vitreous. Periocular depot formulations can prolong drug exposure to the ocular tissues. Understanding ocular barriers and drug pathways after periocular administration is crucial. Abstract : The periocular space is a promising alternative route for the delivery of drugs to the posterior eye segment, especially when treating conditions in the outer ocular layers. In this review, we discuss the different periocular routes as well as the physiological barriers and elimination mechanisms limiting drug bioavailability at the back of the eye. We then highlight various types of depot formulations, including particulate delivery systems, semisolid formulations, and implants, used to increase the contact time with the ocular tissues. With the additional advantage of sustaining drug release, such depot formulations could enhance periocular drug delivery to the posterior eye segment. Teaser: Sustained release formulations administered via the periocular route could provide a more effective approach to treating posterior segment diseases compared with topical drug administration.